The ExoMars Spectral Tool (ExoSpec) : an image analysis tool for ExoMars 2020 PanCam imagery - Allender, Elyse; Stabbins, Roger; Gunn, Matthew; Cousins, Claire R.; Coates, Andrew (Image and Signal Processing for Remote Sensing XXIV, 2019)
This work was supported by the UK Space Agency (ST/P001297/1 and ST/P001394/1). Cousins also acknowledges the Royal Society of Edinburgh for funding. The upcoming launch of the European Space Agency (ESA) ExoMars 2020 rover signals a need for an analysis tool to be created which can exploit the multi- and hyperspectral data that will be returned by its Panoramic Camera (PanCam), Infrared Spectrometer for Mars (ISEM), and Close-UP Imager (CLUPI) instruments. Data processed by this analysis tool will be invaluable in (i) characterising the geology local to the ExoMars rover, (ii) relating ground-based observations to orbital Compact Reconnaissance Imaging Spectrometer for Mars (CRISM) data, (iii) detecting evidence of past habitability on Mars, and (iv) identifying drilling locations. PanCam, ISEM, and CLUPI offer spectral analysis capabilities in both spatial (140-1310 microns/pixel at 2 m working distance) and spectral (440-3300 nm) dimensions. We have developed the ExoMars Spectral Tool (ExoSpec) which functions as a GUI-based extension to ENVI + IDL and performs steps from image import and compilation into ENVI .dat format, flat-fielding, radiometric correction, radiance-toreflectance (R*) corrections using the in-scene Gretag MacBeth ColorCheckerTM, and calculation of spectral parameters. We demonstrate the functionality of ExoSpec at its current stage of development and illustrate its utility with results from field expeditions to Mars analogue terrains in: (i) geothermally altered basalts in N´amafjall, Iceland, and (ii) layered alluvial plains deposits in Hanksville, USA, using ExoMars PanCam, ISEM, and CLUPI emulator instruments.